Hydrogen cyanide and hydrocarbons mix on Titan - Fernando Izquierdo-Ruiz; Morgan L. Cable; Robert Hodyss; Tuan H. Vu; Hilda Sandström; Alvaro Lobato; Martin Rahm (Proceedings of the National Academy of Sciences, 2025)
This work reveals a striking exception to the well-established rule in chemistry that polar and nonpolar compounds do not spontaneously mix: insertion of methane, ethane, and other small hydrocarbons into the crystal lattice of hydrogen cyanide (HCN), a highly polar molecule. By mixing these components at cryogenic temperatures, we can observe distinct shifts in vibrational modes using Raman spectroscopy. Our computational predictions confirm that cocrystal structures of HCN and ethane, which match our experimental vibrational shifts closely, are thermodynamically and kinetically stable. Given that methane, ethane, and HCN are major components of the atmosphere and surface of Saturn’s moon Titan—where they play key roles in shaping chemistry, weather, and landscape—our findings may prove instrumental for explaining Titan’s chemical and geological evolution.